Growth and rupture of an intracranial aneurysm: the role of wall aneurysmal enhancement and CD68+ - Cannizzaro, Delia; Zaed, Ismail; Olei, Simone; Fernandes, Bethania; Peschillo, Simone; Milani, Davide; Cardia, Andrea (Frontiers in Surgery, 2023)
Introduction. Intracranial aneurysms occur in 3-5% of the general population. While the precise biological mechanisms underlying the formation, growth, and sudden rupture of intracranial aneurysms remain partially unknown, recent research has shed light on the potential role of inflammation in aneurysm development and rupture. Additionally, investigations are underway to explore the feasibility of employing new drug therapies for controlling risk factors associated with aneurysms. CD68, a glycosylated glycoprotein and the human homologue of macrosialin, is prominently expressed in monocyte/macrophages within inflamed tissues and has shown potential application in oncology. An observational study was conducted with the aim of comparing histological characteristics of aneurysmsaneurysm walls with pre-operative MRI imaging, with a specific focus on CD68 activity.Method. An observational pilot study was conducted to investigate histological characteristics of the aneurysms wall that could be potentially associated with aneurysmal growth and rupture. A total of t 22 patients with ruptured and unruptured intracranial aneurysms who underwent conventional clipping between January 2017 and December 2022, were enrolled in the study.Results. Histopathological analysis of the aneurysms wall was performed in all patients, with a particular focus on the presence of CD68. Pre-operative MRI with gadolinium was conducted in 10 patients with unruptured aneurysms and 6 patients with ruptured aneurysms. Emergency clipping was performed in the last 6 patients. The results showed that CD68 positivity and wall enhancement were significantly associated with intracranial aneurysm wall degeneration, growth, and rupture.Histological and radiological inflammatory findings observed in the wall of cerebral aneurysms, as well as the CD68 positivity, are significantly associated with the risk of intracranial aneurysm growth and rupture. This study highlights the crucial importance of considering clinical and medical data when making treatment decisions for intracranial aneurysms . Furthermore, it emphasizes the relevance of evaluating wall enhancement in MRI scans as part of the diagnostic and prognostic process.